English as a foreign language textbooks evaluation for tenth-grade students - Is Dewangga; Imam Ghozali (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims (1) to evaluate the English textbooks used for the tenth grade whether the three textbooks have fulfilled the criteria of good textbook and (2) to reveal the strengths and weaknesses of the textbooks. This study was conducted using evaluation research. The theory of evaluation used in this study was the criteria of good textbook proposed by Mukundan, Nimechisalem, and Hajimohammadi (2011) framework. The data were collected through document analysis and interview and analyzed using Miles, Huberman and Saldana’s flow model (2014) of qualitative data research. This study found that Bahasa Inggris X and Pathway to English 1met fourteen criteria of good textbooks proposed by Mukundan, et.al. While, Talk Active X, was met eleventh out of fourteen criteria of good textbooks. Then, the researcher found that the strengths and the weaknesses of the three textbooks. The strengths of Bahasa Inggris X textbooks are (1) provided a teacher’s book, (2) it based on latest 2013 curriculum. The strengths of Pathway to English textbook are (1) provided various methodologies in ELT, and (2) provided audio materials for listening skill. Finally, the strengths of Talk Active X textbook are (1) provided simple task to the complex task, (2) the pictures used in the textbook well matched to the students. Meanwhile, the researcher also found the weaknesses of the three textbooks. Bahasa Inggris X, the weaknesses are 1) did not cover a variety of teaching method, (2) did not provide audio material for listening skill. Furthermore, the weaknesses for Pathway to English are (1) did not provide a teacher’s book; (2) did not match to the syllabus. Finally, Talk Active X textbook, the weaknesses are (1) did not embrace methodologies in ELT; (2) did not support an audio material; (3) did not provide a teacher’s book.